Preventing national identity forgery in Bangladesh using IGA based security controls - Meraj, Afsarul Islam; Samindra, Sadia Ferdous; Chhoan, Tasnim Fuyara; Kashpia, Afsana Sharmily; Ahmed, Tawhid (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.